Efficacy of Drying and Stir-frying to Purple Rice Paddy Herb (Limnophila aromatica) Tea - N. P. Minh (Journal of Global Pharma Technology, 2019)
In Vietnam, L. aromatica is easily cultivated in flooded rice fields. This herb has two very distinct flavours of lemon oil and cumin.  It is used in Vietnamese cuisine to add flavour in soup broths, sauces, and other foods. In order to create a new kind of functional herb tea, we have penetrated on various parameters such as drying and stir-frying the total phenolic and total flavonoid content in the dried stir-fried rice paddy herb tea. Our results revealed that drying raw purple rice paddy herb at 55oC to 8.5% moisture content and then stir-frying at 140oC in 6 minutes could produce the good organoleptic property while maintaining the best phenolic and flavonoid content in this functional beverage. These findings provided useful information for manufactures in processing of this herb to preserve potential sources of bioactive components for consumer and public health. Keywords: Rice paddy herb, Tea, Beverage, Drying, Stir-frying, Phenolic, Flavonoid, Organoleptic.